Quasi-static and dynamic behaviour of monolithic and sandwich beams - Xiang, Xinmei (2016)
Monolithic and sandwich structures are widely used in industries as protective structures. A great deal of data from experiments on monolithic structures under different loading conditions are scattered across engineering literature, so it is necessary to summarize these experimental and analytical results to have a comprehensive understanding of monolithic structures. Monolithic beams with rectangular cross-section have been widely investigated, however beams with different shapes of cross-sections, including circular solid, circular hollow, “I” shaped cross-sections, which are widely used in engineering field, are seldom investigated. In the past few decades, research interest has been shown in studying sandwich structures with various cores, including polymer, foam, honeycombs, prismatic, truss, and textile-based lattice. However, sandwich beams with thin-walled tubes as core which could be used as novel protective structures have seldom been reported. This research work consists of three parts. Firstly, static analyses of beams with different shapes of cross-sections, including circular solid, circular hollow, “I” shaped cross-sections are presented. Monolithic beams are often used as protective structures combined with other energy absorbed such as metal foam and their deformation would be influenced by the foam. The analytical work on a moving monolithic beam rested on a metal foam foundation is also described. Secondly, thin-walled structures have been used extensively in the engineering fields because they can sustain large local and global permanent deformations to absorb plenty of energy under blast loading. Sandwich beams with thin-walled tubes as core could be used as novel protective structures. Quasi-static compressive loadings are applied by using an indenter, to simply supported sandwich beams with three different types of thin-walled tubes as cores. The relationships between the force and displacement are obtained from the experiments. Deformation mechanisms and energy absorption have been analyzed, by studying the energy dissipated in plastic deformation. Furthermore, finite element analyses (FEA) are carried out using ABAQUS and the force and displacement curves are compared with the experimental results. Energy partition is also conducted. It has been found that when the masses of the beams are the same, the smaller the tube diameter is, the larger energy the beam dissipates. Optimized sandwich beam with square tubes has been found to be a desirable candidate as a lighter structure which has the best energy absorption performance among all the structures investigated in this thesis. Finally, experimental investigation and Finite Element (FE) simulations of sandwich beams subjected to transverse blast loads are also conducted. Different masses of TNT with various standoff distances are applied on the sandwich beams respectively. The blast loads are large enough to cause permanent local deformation of the thin-walled tubes and significant plastic global flexural deformation of the entire beams. The FE simulations using Ls-Dyna are compared to the experimental profiles, and an insight into the energy absorption of the local and global deformations as a result of impulsive loading is observed. Finally, the influences of the diameter, the thickness and the number of the circular tubes on the final displacement and the deformation mechanisms are investigated.